Экоморфическое разнообразие и пространственная организация сообщества мезопедобионтов урботехнозема - Кунах, О. Н.; Кунах, О. Н.; Kunah, O.; Жуков, Александр Васильевич; Жуков, Олександр Васильович; Zhukov, A.; Балюк, Ю. А.; Балюк, Ю. А.; Baljuk, Yu.; Федюшко, М. П.; Федюшко, М. П.; Fedyushko, M. (Дніпровський державний аграрно-економічний університет, 2013)
Наведено результати вивчення просторового варіювання екоморфічної структури ґрунтової мезофауни технозему з трав’янистим покривом методами OMI- і RLQаналізу. Ґрунтова мезофауна експериментальної ділянки представлена 26 видами зі загальною щільністю 234,47 екз./м2 . В екологічній структурі тваринного населення ґрунту переважають пратанти та палюданти, гігрофіли, мезотрофоценоморфи, ендогейні та епігейні топоморфи, сапрофаги. Такі едафічні характеристики, як твердість ґрунту, електропровідність, потужність підстилки, а також висота травостою відіграють важливу роль у структуруванні екологічної ніші угруповання мезопедобіонтів. Виявлено чотири ключових функціональних групи мезопедобіонтів і знайдено роль едафічних факторів у їх просторовому варіюванні. The results of studying of the spatial organization of soil mesofauna of the urbanozem of the grassland within artificial forest planting have been processed by OMI- and RLQ-analysis methods. Researches are spent to June, 10st, 2012 in Oles Gonchar University botanic garden (earlier – territory of park of J.Gagarin, Dnepropetrovsk). The studied plot is situated on the Krasnopostachekaya balka valley slope (48°25'56.76"С, 35°2'18.74"В). The plot consists of 15 transects directed in a perpendicular manner in relation to the talveg. Each transect is made of seven sample points. The distance between points is 2 m. The coordinates of lower left point have been taken as (0; 0). The plot represents artificial grassland with single tree. The vegetation has typically forest mega-mesotrophic xeromesophilic character. In each point the soil mesofauna was studied (data presented as L-table); temperature, electrical conductivity and soil penetration resistance, and herbage height were measured (data presented as R-table). Soil-zoological test area had a size of 25×25 cm. The soil mesofauna gave been found as being presented by 26 species and with total abundance 234,47 ind./m2. In ecological structure of the soil animal community have been found such groups dominant as saprohages, pratants and paludants, gygrophiles, mesotrophocoenomorphes, endogeic and epigeic topomorphes. The measured edafic characteristics have been shown to play an important role in structurization of an ecological niche of mesopedobionts community. The usage of morphological or physiological features of animals for an estimation of degree of specific distinctions is applicable for homogeneous taxonomic or ecological groups possessing comparable characteristics which also can be interpreted ecologically. The soil mesofauna is characterized by high taxonomic and ecological diversity of forms and comparing which by morphological or physiological criteria it is rather inconvenient. Ecological sense of characteristics in different groups will be not identical, and the basis for their comparison will be inadequate. Therefore we apply to the description of ecological features ecomorphic analysis of soil animals. The organization of communities of soil animals may be considered at levels of an investigated point, a biogeocenosis, a landscape and regional level. Actually, on the basis of landscape-ecological distribution of species in ecological space their accessory to ecological groups – an ecomorphes is established. The regular ratio an ecomorphes in these functional groups will be reflexion of their organizational structure and an ecological diversity. The obtained data testifies to justice of the come out assumption. It is important to notice that fact that the functional groups allocated in ecological space by means of the RLQ-analysis, show regular patterns of spatial variability. Local functional groups are characterized by ecological characteristics which reflect in terms one ecomorphes of property of others, occupying higher hierarchical position. Ascertaining of spatial heterogeneity of the animal community and determinancy of properties of an ecological niche by soil factors is important result however for understanding of the nature of heterogeneity the spatial variant of ecomorphic the analysis with RLQ-analysis application has been processed. Within comparatively uniform field the spatial differentiation of the animal community on functional groups has been found. The reality of their existence proves to be true not only statistically, but that is especially important, substantial interpretation of ecomorphic markers of groups interrelation and indicators of ecological properties of soil as inhabitancies. The variation of environmental properties within microsites leads to rearrangement of ecological frame of the soil animal community. Heterogeneity of a soil body and vegetation mosaic form patterns of the spatial organisation of the soil animal.
Екоморфічна різноманітність і просторова організація спільноти мезопедобіонтов урботехнозема
Ecomorphic and spatial organisation of the urbanozem mesopedobionts
Keywords: ґрунтова мезофауна; soil mesofauna; екологічна ніша; ecological niche; просторова екологія; spatial ecology; екоморфи; ecomorphes